METHODOLOGY OF FORMING INFORMATION CULTURE IN STUDENTS OF HIGHER EDUCATION INSTITUTIONS - Abduraxmanov Muxtor Xujayarovich, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article talks about the methodology of forming information culture among students of higher education institutions.